2017
DOI: 10.18632/aging.101181
|View full text |Cite
|
Sign up to set email alerts
|

Changes in macroautophagy, chaperone-mediated autophagy, and mitochondrial metabolism in murine skeletal and cardiac muscle during aging

Abstract: Aging causes a general decline in cellular metabolic activity, and function in different tissues and whole body homeostasis. However, the understanding about the metabolomic and autophagy changes in skeletal muscle and heart during aging is still limited. We thus examined markers for macroautophagy, chaperone-mediated autophagy (CMA), mitochondrial quality control, as well as cellular metabolites in skeletal and cardiac muscle from young (5 months old) and aged (27 months old) mice. We found decreased autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 45 publications
6
90
1
Order By: Relevance
“…Aging. Autophagy is an important cellular process involved in aging and longevity that gradually declines during cardiac aging, resulting in an increase in the sensitivity of the heart to stress [24]. Autophagy is a catabolic process involved in lifespan and aging in the cardiovascular system [25].…”
Section: Autophagy In Cardiacmentioning
confidence: 99%
“…Aging. Autophagy is an important cellular process involved in aging and longevity that gradually declines during cardiac aging, resulting in an increase in the sensitivity of the heart to stress [24]. Autophagy is a catabolic process involved in lifespan and aging in the cardiovascular system [25].…”
Section: Autophagy In Cardiacmentioning
confidence: 99%
“…Total RNA isolation from cultured cells and liver tissue was performed using InviTrap Spin Universal RNA kit (Stratec Biomedical, Birkenfeld, Germany), and RT-qPCR was performed as described previously [54] using QuantiTect SYBR Green PCR kit and KiCqStart SYBR Green optimized primers from Sigma-Aldrich (KSPQ12012).…”
Section: Mrna Expression Analysis By Reverse Transcription-quantitatimentioning
confidence: 99%
“…Interestingly, studies have found that macroautophagy capacity seems to decline with age, as indicated by lower levels of autophagy biomarkers, such as Atg7 and LC3‐II/I ratio, and an increase in protein levels of p62 and Bnip3 in aged mice and humans . Similar to muscle specific Atg7 knockout mice, it is possible that age‐related muscle atrophy is not necessarily due to impaired macroautophagy in skeletal muscles, but compensatory response, such as apoptosis, promoted by the impairment of autophagy.…”
Section: The Mammalian Target Of Rapamycin (Mtor)/protein Kinase B (Amentioning
confidence: 99%